Bagging Up - Richardson, Lisa (UnderCurrents: Journal of Critical Environmental Studies, 1999)
At night we sit around the mess tent and even the non-smokers smoke because we need to indulge and the head rush is great after a day of hard work. We share stories. About the land. About the tree prices. About a granite hill which we have to plant tomorrow. About a crazy day a couple of years ago when someone was supposed to plant a quicksand strip out in Alberta. About a woman from BC who planted 10,000 trees in a single day ... [...]